PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IVB SDN 136 PEKANBARU - Komara, Fajriah Hasanah Tri; Putra, Zetra Hainul; Hermita, Neni (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2020)
This research is motivated by the low mathematics learning outcomes of fourth grade students of SD Negeri 136 Pekanbaru, with an average score of 68.25 and only 17 of 40 reach the minimum completeness criteria (KKM). This research is a classroom action research (CAR) conducted aimed at improving the mathematics learning outcomes of fourth graders by implementing a cooperative model of picture and picture type. The subjects of this study were 40 fourth grade students of class IVB in 2019/2020 school year. Data collection instruments in this study were teacher activity sheets and student activities and learning outcomes. The results of this study indicate that student learning outcomes increased by 13.26% from an average of 68.25 to 77.3 in cycle I. In the second cycle it increased to 24.54% with an average of 85. Teacher activity also increased from 75 .00% with enough category in the first cycle of the first meeting to be 96.43% very good category in the second meeting of the second cycle. The results showed that the application of the Cooperative model type Picture and picture could improve the mathematics learning outcomes of class IVB students of SD Negeri 136 Pekanbaru.